Effects of improved water flow on the aquatic environment and wastewater composition in sewage-fed fisheries of India - Pankaj Kumar Roy; Arunabha Majumder; Asis Mazumdar; Mrinmoy Majumder; Malabika Biswas Roy (Advances in Aquaculture and Fisheries Management, 2023)
In this study, we estimated the impact of enhanced flow on shallow wetlands that receive major effluent discharge from an adjoining metropolitan city. The local people use the shallow wetlands for pisciculture. Beginning in 1998, the population of the city began to rise and the amount of effluent discharge increased. The excess load is now a problem for the city engineers, and they plan to manage the sewage by increasing the area of the sewage network. The depth of the wetlands is also decreasing due to an increase in suspended solids. The quantity of the toxic load suspended in the discharge has increased the silt content, which has consequently further reduced the depth of the wetlands. The excess flow on low depth wetlands may cause overflows and destroy both the ecosystem and the livelihood of the local people. In this study, the pattern identification capability of neuro-genetic models was used to estimate the impact of the excess flow on sewage-fed wetlands. Two neural network models were created to estimate whether fisheries can accommodate the enhanced flow. According to the results of this study, the East Kolkata Wetlands, India can accommodate 1450 million litres per day (MLD) of sewage, if the average depth of water is increased to 1.18 m.